Co-digestion strategies of rice straw and molasses for biohythane production: a techno-economic evaluation - Sencan, Serpil; Ozturk, Abdullah Bilal; Gulen, Jale (TAYLOR & FRANCIS LTD, 2026)
Rising environmental concerns and the growing demand for sustainable energy solutions have accelerated the transition toward bio-based alternatives. Among the renewable energy sources, biogas and biomethane possess significant properties for clean energy, and biohythane, a mixture of biohydrogen and biomethane, has emerged as a promising biofuel produced through the anaerobic fermentation of organic waste. However, one of the critical barriers to the scalability of bioprocesses is the financial viability of plants and validation by reasonable decision-making economic indicators. To this end, this study assesses the techno-economic feasibility of biohythane production by co-utilizing rice straw and sugarcane molasses as feedstocks. A two-stage dark fermentation and anaerobic digestion process was simulated using SuperPro Designer (R). The economic performance was evaluated based on key indicators, including net present value (NPV), internal rate of return (IRR), return on investment (ROI), gross margin (GM), and payback period. The results demonstrate that the proposed system is economically viable, with an NPV of $1.7 million, a GM of 36.84%, an ROI of 5.08%, an IRR of 0.40%, and a payback period of 12.03 years. This study underscores biohythane's potential as a renewable energy source while also contributing to waste management and promoting a circular economy.
Keywords: Techno-economic analysis; biohydrogen; biomethane; biohythane; process simulation; FERMENTATIVE HYDROGEN-PRODUCTION; 2-STAGE ANAEROBIC-DIGESTION; OIL MILL EFFLUENT; WASTE VALORISATION; CH4 PRODUCTION; LACTIC-ACID; FOOD; BUTANOL; LACTATE; DESIGN; Energy & Fuels